National Culture and Leadership in the United Arab Emirates (UAE) - MORADKHAN, EALBRA (2012)
With the trend towards globalisation, multinational corporations continue to seek global diversity. As such it is imperative to better understand the importance and impact of organisational variables such as leadership and culture on organisational performance and productivity. Globalisation and transferability of human capital across the globe has stimulated an increasing need to develop global managers who understand the implications of cross-cultural work environments and are able to effectively manage people from different cultural backgrounds with diverse cultural values and practices to achieve business success. National culture (NC) has an overwhelming power to influence people’s behaviour both at society and organisational levels. This study examined how NC and its dimensions influenced the leadership behaviour of the managers in the United Arab Emirates (UAE). The dimensions of NC and leadership used in this study were the ones developed by House et al. (2004) for Project GLOBE. The survey covered a number of managers and senior employees in the Marine and Oil & Gas sectors from a variety of countries. The collected data from the sample was analysed using a number of statistical tests. The results of this study confirmed a positive correlation between NC and leadership behaviour of managers in the UAE. However more specifically the study revealed that Charismatic, team oriented, humane oriented and autonomous leadership behaviours are culturally endorsed whereas self- protective and participative leadership behaviours are significantly correlated to NC. Leadership is a competitive advantage that influences organisations’ sustainable performance results. In order to enhance leadership abilities of the managers in a diverse cultural environment such as the UAE, this study has made recommendations in relation to ‘organisational culture’, ‘recruitment & selection’ and ‘leadership development’. Organisational culture can be referred to as a micro model of national culture, hence a strong organisational culture will outline the expected behaviour of the leaders and other members that are perceived to contribute towards organisational performance and success. In addition to that, this study also recommends evaluating underlying intellect and interpersonal skills of the candidates for leadership roles along with their technical skills and experience in order to have a comprehensive assessment of one’s leadership potential. And finally, the study recommends that organisations should hold all the senior executives and line managers accountable for the development of individual managers by owning and executing succession plans.